Pretexting and means to counter it - U. A. Mikhaleva (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. Currently, fraud is one of the most pressing problems in modern society. The number of victims of scammers using social engineering methods is growing day by day. Because fraud is a type of crime that is very difficult to prove. The aim of the study is to find a method to counteract pretexting as an increase in the information security of the population.Method. This article uses the following methods: description, analysis, deduction.Result. The analysis of the description of social engineering methods made it possible to classify them according to the way they influence a person. Also, this analysis led to the conclusion that the most effective method to protect against the threats of social engineering, in particular, from pretexting, is the introduction of technical methods of protection.Conclusion. The conclusions made in this work can serve as a basis for further research in this direction, as well as the basis for the development and implementation of technical methods for protecting against pretexting threats.